INVESTIGATING THE FACTORS INFLUENCING STUDENTS' WILLINGNESS TO COMMUNICATE IN ENGLISH - Zuhrufi Latifah; Dadang Sudana; Fazri Nur Yusuf (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
This paper aims to investigate the factors that affect the students’ willingness to communicate in English in the classroom. This study employs a qualitative method, particularly the case study with the use of observation, questionnaire, and interview to collect the data. It can be concluded that there are mainly five factors that influence students’ willingness to communicate namely teachers, topic discussions, classroom environment, peers, and types of activities.